High level performance in world judo circuit: Notational analyzes of combat phase by weight categories - Lopez Diaz-de-Durana, A.; Dal Bello, F.; Brito, C. J.; Miarka, B. (Journal of Human Sport & Exercise, 2018)
This studyanalysed the time dedicated in the different phases of combat in all male weight divisions. For this, we analysed 548 combats. This time-motion analysis was performed through a previously-validated protocol. The main results indicated a significant effectfor approach (p=0.001), where the Half-Middleweight division showed a higher frequency vs. the others, except Half-heavyweight. For attack, Half-Lightweight showed a higher frequency versus Heavyweight (5.7±4.8 vs. 4.6±3.5 attempts; p=0.004). Extra-Lightweight showed a lower frequency of defences vs Half-Lightweight and Lightweight (2.2±2.6 vs. 3.8±3.2 vs. 4.4±3.7 attempts; (p=0.047). Extra-Lightweight also showed a lower frequency of standing to ground transition vs. Half-Lightweight, Lightweight, and Half-Middleweight (p=0.048). For groundwork, Middleweight showed a lower frequency of actions vs. the other divisions, except Heavyweight (p=0.001). for the pause the Heavyweight division showed a lower frequency vs. Lightweight and Half-Middleweight (6.7±4.2vs. 9.9±6.2 vs. 10.2±6.3 times; p=0.019). In conclusion, our results can be applied to planning and prescribing specific training for the different weight divisions, taking into account the specific frequencies obtained in the combat phases. Forlighter fighters, we recommend training focused on approach speed and gripping. For heavier weights, the training should be differentiated for muscle power development and groundwork combat.